The relation between H.C.F. and L.C.M. of two polynomials is the product of the two polynomials is equal to the product of their H.C.F. and L.C.M.
If p(x) and q(x) are two polynomials, then p(x) ∙ q(x) = {H.C.F. of p(x) and q(x)} x {L.C.M. of p(x) and q(x)}.
= a(a – 7) – 1(a – 7)
= (a – 7) (a – 1)
Therefore, the H.C.F. = (a – 7) and L.C.M. = (a – 7) (a – 5) (a – 1)
Note:
(i) The product of the two expressions is equal to the product of their factors.
(ii) The product of the two expressions is equal to the product of their H.C.F. and L.C.M.
Product of the two expressions = (a^{2} – 12a + 35) (a^{2} – 8a + 7)= (a – 7) (a – 5) (a – 7) (a – 1)
= (a – 7) (a – 7) (a – 5) (a – 1)
= H.C.F. × L.C.M. of the two expressions
= a(a + 9) + 1(a + 9)
= (a + 9) (a + 1)
Therefore, the H.C.F. = (a + 9)
Therefore, L.C.M. = Product of the two expressions/H.C.F.
= \(\frac{(a^{2} + 7a  18) (a^{2} + 10a + 9)}{(a + 9)}\)
= \(\frac{(a + 9) (a  2) (a + 9) (a + 1)}{(a + 9)}\)
= (a – 2) (a + 9) (a + 1)
Solution:
According to the problem,
Required Expression = \(\frac{L.C.M. × H.C.F.}{Given expression}\)
= \(\frac{(m^{3}  10m^{2} + 11x + 70)(x  7)}{x^{2}  5x  14}\)
= \(\frac{(m^{2}  5m  14)(x  5)(x  7)}{x^{2}  5x  14}\)
8th Grade Math Practice
From Relation Between H.C.F. and L.C.M. of Two Polynomials to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.